Recovery definitions: Do they change?. (1st September 2015) - Kaskutas, Lee Ann; Witbrodt, Jane; Grella, Christine E.
Highlights: There is no empirically validated definition of recovery to guide the field. We study the stability of recovery definitions from 1237 recovering individuals. Definitions supported at baseline continue to be widely accepted 1–2 years later. Providers can use these stable definitions to develop recovery support services. Definitions give researchers an alternative to defining recovery just as abstinence. Abstract: Background : The term "recovery" is widely used in the substance abuse literature and clinical settings, but data have not been available to empirically validate how recovery is defined by individuals who are themselves in recovery. The "What Is Recovery?" project developed a 39-item definition of recovery based on a large nationwide online survey of individuals in recovery. The objective of this paper is to report on the stability of those definitions one to two years later. Methods : To obtain a sample for studying recovery definitions that reflected the different pathways to recovery, the parent study involved intensive outreach. Follow-up interviews ( n = 1237) were conducted online and by telephone among respondents who consented to participate in follow-up studies. Descriptive analyses considered endorsement of individual recovery items at both surveys, and t -tests of summary scores studied significant change in the sample overall and among key subgroups. To assess item reliability, Cronbach's alpha was estimated. Results : Rates of endorsement of individual items at both interviews was above 90% for a majority of the recovery elements, and there was about as much transition into endorsement as out of endorsement. Statistically significant t -test scores were of modest magnitude, and reliability statistics were high (ranging from .782 to .899). Conclusions : Longitudinal analyses found little evidence of meaningful change in recovery definitions at follow-up. Results thus suggest that the recovery definitions developed in the parent "What Is Recovery?" survey represent stable definitions of recovery that can be used to guide service provision in Recovery-Oriented Systems of Care.